2010
DOI: 10.1111/j.1755-5949.2010.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

HPA Axis Alterations in Mental Disorders: Impact on Memory and its Relevance for Therapeutic Interventions

Abstract: Dysfunctions in hypothalamic-pituitary-adrenal (HPA) axis have been reported for several mental disorders that are also often characterized by memory disturbances. It is now well established that glucocorticoids influence cognitive processes by enhancing memory consolidation and impairing memory retrieval. There is further evidence for an association between HPA axis related disturbances and memory function in mental disorders. The present selective review provides a brief overview of HPA axis dysfunction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 148 publications
1
60
2
Order By: Relevance
“…This is important because in the case of hydrocortisone, it has clearly been shown that it enhances memory consolidation but impairs memory retrieval in healthy subjects (Wingenfeld and Wolf, 2011). However, our results indicate that the net effect of fludrocortisone was beneficial on memory systems, although on verbal memory only with regard to the learning curve on trend-level significance.…”
Section: Discussioncontrasting
confidence: 66%
“…This is important because in the case of hydrocortisone, it has clearly been shown that it enhances memory consolidation but impairs memory retrieval in healthy subjects (Wingenfeld and Wolf, 2011). However, our results indicate that the net effect of fludrocortisone was beneficial on memory systems, although on verbal memory only with regard to the learning curve on trend-level significance.…”
Section: Discussioncontrasting
confidence: 66%
“…Finally, in our design, we were not able to clearly distinguish between fludrocortisone effects on memory acquisition, consolidation, and retrieval. This is important because in the case of hydrocortisone it has clearly been shown that it enhances memory consolidation but impairs memory retrieval in healthy subjects (Wingenfeld and Wolf, 2011). However, our results indicate that the net effect of fludrocortisone was beneficial on verbal memory as well as on executive function.…”
Section: Discussioncontrasting
confidence: 56%
“…They were medication-free (except of oral contraceptives) and were combined into one group according to the transdiagnostic theory of EDs [47]. Due to well-known changes in HPAA activity in post-traumatic stress disorder, borderline personality disorder or schizophrenia [59,60], patients with EDs fulfilling the criteria of at least one of those diagnoses were excluded. Duration of illness was not restricted but considered in subsequent analyses.…”
Section: Participantsmentioning
confidence: 99%